Cerebellar Transcranial Direct Current Stimulation for Learning a Novel Split-belt Treadmill Task: A Randomised Controlled Trial - Kumari, N; Taylor, D; Rashid, U; Vandal, AC; Smith, PF; Signal, N (Nature Publishing Group, 2020)
This study aimed to examine the effect of repeated anodal cerebellar transcranial direct current stimulation (ctDCS) on learning a split-belt treadmill task. Thirty healthy individuals randomly received three consecutive sessions of active or sham anodal ctDCS during split-belt treadmill training. Motor performance and strides to steady-state performance were evaluated before (baseline), during (adaptation), and after (de-adaptation) the intervention. The outcomes were measured one week later to assess absolute learning and during the intervention to evaluate cumulative, consecutive, and session-specific effects. Data were analysed using linear mixed-effects regression models. During adaptation, there was no significant difference in absolute learning between the groups (p > 0.05). During de-adaptation, a significant difference in absolute learning between the groups (p = 0.03) indicated slower de-adaptation with anodal ctDCS. Pre-planned secondary analysis revealed that anodal ctDCS significantly reduced the cumulative (p = 0.01) and consecutive-session effect (p = 0.01) on immediate adaptation. There were significant cumulative (p = 0.02) and session-specific effects (p = 0.003) on immediate de-adaptation. Repeated anodal ctDCS does not enhance motor learning measured during adaptation to a split-belt treadmill task. However, it influences the maintenance of learnt walking patterns, suggesting that it may be beneficial in maintaining therapeutic effects.
Keywords: Randomized controlled trials; Therapeutics